Organizational Happiness Character (OHC) On Lecturer Performance: Mediating Organizational Commitment - Granit Agustina (Jurnal Ilmiah Manajemen Kesatuan, 2025)
One important aspect in improving the ranking of higher education institutions is the institutional conditions of higher education institutions, these conditions greatly influence the improvement of lecturer performance. One of the factors assumed to be able to improve lecturer performance is the organizational happiness character (OHC). This study aims to determine the effect of the role of OHC on lecturer performance mediated by organizational commitment (OC). The study was conducted on private university lecturers throughout Greater Bandung. The population was 5,475 lecturers, the research sample was at least 200 lecturers obtained from 21 private universities throughout Greater Bandung. Data collection was carried out using a questionnaire with a semantic differential scale. The data analysis technique used SEM-AMOS. The study was conducted to analyze lecturers' perceptions of OHC, organizational commitment, and lecturer performance, by testing 4 research hypotheses. The research hypothesis shows that there is a positive and significant relationship between OHC and lecturer performance, OHC and organizational commitment are also proven to be positive and significant, organizational commitment has a significant positive effect on improving lecturer performance. This study also shows that organizational commitment has a partial mediation effect in improving lecturer performance. Thus, it can be said that the OC variable is a mediator of the influence of the OHC variable on employee performance.